The Impact of Multicomponent Lifestyle on Self-Efficacy in Stable Chronic Obstructive Pulmonary Disease (COPD) Patients - Dewi Kartika Sari; Nopan Saputra; Yance Komela Sari; Astilia Astilia (Indonesian Journal of Global Health Research, 2024)
Chronic Obstructive Pulmonary Disease (COPD) is a global issue that continues to persist today. This is due to the increasing incidence and mortality rates of COPD worldwide from year to year. The aim of this study is to determine the effect of multicomponent lifestyle education on the self-efficacy of stable Chronic Obstructive Pulmonary Disease (COPD) patients at Rasyidin Hospital in Padang. This study is a quasi-experimental research with a control group design. The population in this study consists of 111 stable COPD patients at the Pulmonary Outpatient Clinic of Rasyidin Hospital Padang, all of whom are receiving outpatient services. The sample size in this study was 66 respondents, divided into two groups of 33 individuals each: the intervention group and the control group. Data analysis was conducted using a paired t-test with a significance level of 0.05. In the intervention group, it was found that multicomponent lifestyle education had an effect on self-efficacy, with a p-value of 0.000.